PSV-6 A survey of New England sheep producers. (7th December 2018) - Halpern, A; Kelly, M; Hoffman, M; Jones, A; Bonelli, J; Zinn, S; Reed, S; Govoni, K
Abstract: Maternal nutrition during gestation impacts offspring BW, body composition, and metabolism, thereby affecting productivity. Several sources of information are available to producers for guidance in managing their breeding flocks; however, it is unknown if sheep producers in New England utilize these resources. In previous USDA surveys of sheep producers, New England was not included, thus leaving a gap of knowledge. Our objective was to conduct a survey of New England sheep producers to determine flock size, breeds, pregnancy detection methods, feeding management practices, and producer learning styles. In particular, we wanted to determine if flock size influenced management practices, and if flock purpose (eg., meat, fiber) and feed type (eg., hay) influenced feed management. A 12-question survey was developed and disseminated via Qualtrics using e-mail survey links, with a 33.2% response rate (n = 96 responses). Data were analyzed using SPSS. Of the respondents, 61.5% had flocks sizes of 11 to 50 sheep. Most producers (63.5%) maintain 1 breed of sheep; however, larger flocks (> 50 sheep) are more likely to maintain multiple breeds (P < 0.05). The majority (79.2%) use their sheep for meat production, 61.5% for fiber, and 37.1% manage sheep for both. Spring (January to May) is the primary (59.4%) lambing season. The majority (76.0%) of New England sheep producers do not analyze their feed, which presents an opportunity for improved outreach. There were correlations (P < 0.05) between flock size and flock purpose, flock size and number of breeds owned, flock size and feed type, feed types and number of feed types used, feed type and feed analysis, and source of feed information. In conclusion, New England sheep producers have flocks of varying size and purpose, and would likely benefit from outreach education on the benefits of diet analysis and formulation for their breeding flocks.